HOW ESP PEDAGOGY IN INTERNATIONAL VIRTUAL COLLABORATION CONTRIBUTES TO THE AUTHENTICITY OF THE LEARNING PROCESS: A CASE STUDY - Wendy Winn; Katalin Beck (Informascope, 2018)
Given the rapid advances in information communication technology (ICT) and the ever-increasing likelihood that students will be collaborating on cross-cultural teams in their future careers, creating opportunities to engage in collaborative writing projects across borders and then observing the dynamics of international virtual online collaboration have high pedagogical value, though studies are scarce. This research examines the learning process that occurred when engineering and computer science students from France and Germany were connected with business and technical writing students from the US to work on co-authored documents. The researchers were specifically interested in how students addressed the situational constraints of the collaboration and how those constraints influenced students' choices of communication and collaboration tools. Two separate projects were assigned and each employed reading, writing, "talking," and critical thinking components. Analysis of post-project survey data and the correlation of students' ICT choices revealed students had to continually renegotiate their communication and collaboration. Allowing students to make rhetorical choices resulted in cultural learning through hands-on experience with these constraint variables: English language proficiency, cultural differences, project complexity, time difference, and technology. The results from this study will be useful to ESP pedagogy in projecting how to prepare students for international virtual collaboration.